Women's empowerment through domestic waste management in Dagan Village, Purbalingga Regency - Saputri, Apik Anitasari Intan; Ayu, Nurina (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
In villages, empowering women to manage household waste is a crucial tactic to create a hygienic and safe environment and enhance communal well-being. When given the proper assistance, women may contribute significantly to the creation of ecologically friendly and sustainable communities.. This essay attempts to educate women about managing household garbage. Additionally, in order to resolve environmental problems, a suitable legal approach strategy is required, utilizing the Law (UU) Number 32 of 2009 concerning Environmental Protection and Management to its fullest potential. A fundamental tenet of community empowerment, the Asset-Based Community Development (ABCD) approach, which is used in this qualitative study, focuses on the assets and strengths of the community. The findings of this research, the method for village empowerment; (1) Village mapping. Women's empowerment through domestic waste management in Dagan Village by involving the community in identifying their village assets, potentials, and challenges, (2) Participatory planning. (3) Local capacity development. (4) Holistic approach and (5) Multi-stakeholder partnership: Involving various parties, such as the government, the private sector, NGOs, and academics, in supporting the empowerment of Dagan village women. By implementing the right strategies and focusing on community participation, villages can achieve sustainable empowerment and improve community welfare effectively.